Triisopropylsilylethynyl-Pentacene on Au(111): adsorption properties, electronic structure, and singlet fission dynamics - Stein, Arnulf; Maaß, Friedrich; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2017)
Oligoacenes have recently received much attention because of their ability to undergo singlet fission, a process which may improve the energy conversion efficiency in organic solar cells. Here, we studied the structural and the electronic properties of triisopropylsilylethynyl-pentacene (TIPS-Pn) adsorbed on Au(111) from monolayer to multilayer coverages using multiexperimental techniques [temperature-programmed desorption, vibrational and electronic high-resolution electron energy loss spectroscopy, and energy- and time-resolved two-photon photoemission (2PPE)]. We demonstrated that well-defined TIPS-Pn molecular films can be prepared via evaporation. TIPS-Pn adopt on Au(111) a molecular adsorption geometry in which the pentacene backbone is oriented parallel to the substrate. We determined the energetic position of several unoccupied and occupied electronic states among others originating from the lowest unoccupied molecular orbital and the highest occupied molecular orbital. Femtosecond time-resolved 2PPE enabled us to resolve the time scales for the singlet fission process, which are coverage-dependent. The present study provides important parameters such as energetic positions of molecular electronic states as well as the electronically excited-state dynamics involved in the singlet fission process, which are essential for designing organic-molecule-based optoelectronic devices.
Published online: 9 August 2017
Gesehen am 14.09.2018